Reflective Gem to Improve Receptive Communication Skills for Students with Hearing Impairment - Fitria, Erlin; Hardiyantari, Oktavia (Universitas Islam Negeri Raden Intan Lampung, 2021)
The inability to receive excitatory voice experienced by the student with hearing impairments presents diverse impacts. The impacts include difficulties in understanding the information that others convey, lengthy understanding sentences, and holding verbal communication. This research aimed to develop a reflective maternal method integrated with the Android system to improve vocabulary mastery to support students with hearing impairments to perform receptive communication. There were twelve students with hearing impairments within the 15-23 age range as the samples. This research belongs to research and development adapted from the multimedia development model for learning. Product feasibility test was performed through the alpha and beta tests. The average expert validation score was 4.25, and the average score of the material expert was 4.50. Both expert validation results were in an excellent category. Also, the results of the media experts' validation were 3.58 in the good category. Meanwhile, the average score of beta test was 3.58 in the good category. It can be concluded that Android apps can be operated via smartphones or computer devices to improve the receptive communicative ability of students with hearing impairments. This application is called Reflective Game. This research recommends an Android application program that can be used by Guidance and Counseling teacher accompanied by special school teachers to improve students' vocabulary understanding for the student with hearing impairment. Besides, it provides skills to understand proverbs, opposites (anonymous), and synonyms.